Magnetic resonance imaging in the assessment of fetal central nervous system anomalies - Salkić, Edina (Medical imaging and radiotherapy journal, 2021)
Introduction: Fetal CNS anomalies are among the most severe and common anomalies with an incidence of 1: 100 to 1: 500 in newborns, and depending on the type of anomaly, the diagnosis can only be made at certain periods of pregnancy. The prenatal US is an effective primary imaging modality for the depiction of these anomalies, and MRI is a method that provides useful confirmation and resolves the suspicion of the diagnosis made on prenatal ultrasound. In situations where ultrasound examination is difficult, fetal MRI can provide superior information, thanks to its many advantages. The aim of this study was to determine the importance of prenatal MRI in making an accurate diagnosis and assessment of fetal CNS anomalies after neurosonographic suspicion, and in detecting additional anomalies missed on ultrasound, which influences clinical decision making and anomaly outcomes. Material and methods: For this research, which was designed as a systematic review of the primary scientific research literature, numerous articles were used, i.e.17 scientific research papers, published within the relevant scientific research online databases such as PubMed, Medline, Google Scholar, and the same were published in English in the period from 2015 to 2021. Results: From the assessment of the quality of studies with cohort design it can be concluded that most of the studies used in this systematic review are in the category of high-quality studies (11 in total), with a smaller number of medium-quality studies (6 in total). In a total of 575 cases, MRI confirmed the ultrasound diagnosis and agreed with it in 59.8% of cases, while in 20.2% of cases it changed the diagnosis, i.e. in 16.5%, it rejected the ultrasound diagnosis. Additional anomalies detected only on MRI occurred in 236/1225 cases, which totals 19.3% of additional anomalies. Termination of pregnancy was reported in 82/317 cases, accounting for 25.9%, while in a total of 176 cases the pregnancy continued. A total of 11 cases of neonatal death were reported, and the number of stillbirths or deaths after birth was reported in 8 cases. Conclusion: MRI using T2W SSFSE sequences in 3 planes, T1W and DWI in the axial plane is a complementary modality to prenatal ultrasound in making an accurate diagnosis and assessment of CNS anomalies, and detecting associated anomalies previously missed on ultrasound.
Keywords: anomalije centralnega živčnega sistema ploda; fetal central nervous system anomalies; fetal magnetic resonance imaging; fetal neurosonography; fetalna magnetna resonanca; fetalna nevrosonografija